Protection of Civilians and Human Right Violations : A Critical Examination of International Humanitarian Law in the Russo-Ukrainian Conflict - Ou, Julia (Transactions on Social Science, Education and Humanities Research, 2023)
International humanitarian law crimes committed during the war between Russia and Ukraine are the focus of this article. The war’s beginnings, evolution, and effects on both residents and visitors are examined. This article gives a brief introduction to the fundamental concepts of IHL and describes how these principles apply to the safeguarding of civilians in times of war. Whether or whether international humanitarian law was observed throughout the war between Russia and Ukraine is investigated. Human rights violations and the role of international humanitarian law in safeguarding people are also discussed. The results emphasize the significance of political will in protecting international law, and the necessity for improved IHL enforcement measures.